Mobile Application for Drug Abuse Prevention among Teenagers: Effectiveness in Bandung City - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (West Science Interdisciplinary Studies, 2025)
This study explores the effectiveness of a mobile application designed to prevent drug abuse among teenagers in Bandung City using a qualitative approach. The research involved five teenage informants aged 15–18 years who had used the application for at least one month. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that the application significantly increased awareness about the dangers of drug use, improved self-confidence in resisting peer pressure, and encouraged the sharing of knowledge within peer groups. Additionally, the app’s interactive and gamified features contributed to a positive learning experience. However, suggestions for improvement included the need for real-time support and more localized content. Overall, the study highlights the potential of mobile technology as an innovative tool in youth-focused drug abuse prevention efforts, especially when designed with user engagement and cultural relevance in mind.